2018
DOI: 10.1021/acsomega.8b00325
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Combing of a Flexible Polymer Chain by Simple Spin-Casting

Abstract: If polymer chains could be fixed on a substrate as a fully elongated chain, a procedure known as “ molecular combing ”, the chain structure could be analyzed more precisely than has been possible with the characterization techniques available today. Although the molecular combing of a rigid biomolecule, DNA, has been attained for the mapping of genetic information, that of flexible chains has never been achieved as yet. We show here that poly( n -nonyl acrylate) (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…As mentioned in the Introduction, we reported that the PNA chains were molecularly combed as close to the all-trans conformation by spin-casting a chloroform solution on mica . We first explored the conditions under which molecular combing was attained by the dipping method using PNA and found that the PNA chains could be molecularly combed by the dipping method under optimized conditions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As mentioned in the Introduction, we reported that the PNA chains were molecularly combed as close to the all-trans conformation by spin-casting a chloroform solution on mica . We first explored the conditions under which molecular combing was attained by the dipping method using PNA and found that the PNA chains could be molecularly combed by the dipping method under optimized conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Chloroform is a good solvent for all the polymers studied here. In the chloroform solution, with an increase in the length of the alkyl group in the side chain, the polymer chains moderately expand due to steric hindrance between the long side alkyl chains, but the expansion ratio is rather moderate and still leads to random coils [see Sections 3–6 in ref ]. It is rational to think that the molecular combing occurred during the dipping process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations